2020
DOI: 10.3892/etm.2020.8946
|View full text |Cite
|
Sign up to set email alerts
|

Histological and ultrastructural changes of the colon in dextran sodium sulfate‑induced mouse colitis

Abstract: Ulcerative colitis (UC) is a complex disease that results from a dysregulated immune response in the gastrointestinal tract. A mouse model orally administered with dextran sodium sulfate (DSS) is the most widely used experimental animal model of UC. However, the ultrastructure of the colon in mouse colitis is poorly understood. In the present study, colonic specimens from DSS-induced UC mice underwent hematoxylin and eosin staining, Masson's trichrome staining and Verhoeff's elastic staining. In addition, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
22
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 33 publications
4
22
0
1
Order By: Relevance
“…Analysis of the submucosa revealed significant edema and inflammatory cell infiltration. Our results were in line with previous work [ 24 , 25 ].…”
Section: Discussionsupporting
confidence: 94%
“…Analysis of the submucosa revealed significant edema and inflammatory cell infiltration. Our results were in line with previous work [ 24 , 25 ].…”
Section: Discussionsupporting
confidence: 94%
“…Through the evaluation of colonic histomorphometry and antioxidant enzyme activity, we observed that treatment with FMRP improved IBD in the present study. In part, inflammatory cell infiltration has led to submucosal edema and collagen fiber disruption [ 45 ]. Oxidative stress contributes to the initial stage of the progression of colorectal diseases, and antioxidant enzymes such as CAT, SOD, and Gpx play important roles in IBD.…”
Section: Discussionmentioning
confidence: 99%
“…Histological/ultrastructural changes of the colon in DSS-induced colitis is represented mainly by the presence of damaged goblet cell architecture in the mucosa, a significant infiltration of inflammatory cells into the stroma as well as destruction of the intestinal gland structure. Moreover, the tissue in the submucosa very often shows significant signs of oedema and hyperplasia [ 65 ]. In terms of immune cells, the infiltration of neutrophils and macrophages is observed as early as on the first day after chemical stimulation, and it is increased over time [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, mucosal changes of the large intestine involving the rectum were localised especially in the distal colon with decreasing severity towards the proximal part. Histological examination of colonic sections revealed an altered architecture of colon mucosa with typical inflammatory changes in DSS group [ 65 ] whereas faecal transplant had protective effects and was able to restore histopathological changes in the colon possibly due to rebalanced intestinal microbiota. Similar results were obtained in human studies where FMT improved the scores for diarrhoea and mucous membrane lesions in patients with UC [ 67 , 68 ].…”
Section: Discussionmentioning
confidence: 99%